К вопросу о роли гласных и согласных в звуковых традициях русского и туркменского языков - Иванова, Т.А.; Винниченко, С.Д.; Гурмурадова, С.; Іванова, Т.А.; Вінніченко, С.Д.; Гурмурадова, С.; Ivanova, T.A.; Vinnichenko, S.D.; Gurmuradova, S. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2011)
В статье дается анализ роли гласных и согласных звуков в русском и туркменском языках.
До питання про роль голосних та приголосних у звукових традиціях російської та туркменської мов
For the question about part of vowel and consonant at the sound tradition of Russian and Turkmen languages
The analysis of vowel’s and consonant’s part at Russian and Turkmen languages has been given in this article.
Keywords: артикуляция; фонема; фонологическая система; артикуляція; звук; фонема; фонологічна система; articulation; sounds; phoneme; system of phonemes of a language